2001
DOI: 10.1002/jca.10005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of women with clinically suspected thrombotic thrombocytopenic purpura‐hemolytic uremic syndrome during pregnancy

Abstract: Thrombotic thrombocytopenic purpura-hemolytic uremic syndrome (TTP-HUS) is more common in women, and commonly occurs during pregnancy and the immediate postpartum period. An important clinical issue is the distinction of TTP-HUS from the more common obstetric complications, preeclampsia and HELLP syndrome (hemolysis, elevated liver function tests, low platelets). Clinical suspicion of TTP-HUS requires urgent intervention with plasma exchange treatment, a procedure with substantial risk, while preeclampsia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
89
1
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 46 publications
0
89
1
5
Order By: Relevance
“…Several studies show that 10-31% of TTP occurs in pregnant women [3,4], suggesting that pregnancy may have a triggering effect in the pathogenesis of TTP. Pregnancy may sensitize the endothelial cells to cytotoxic agents, or it may interfere with the release and/or degradation of von Willebrand factor multimers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that 10-31% of TTP occurs in pregnant women [3,4], suggesting that pregnancy may have a triggering effect in the pathogenesis of TTP. Pregnancy may sensitize the endothelial cells to cytotoxic agents, or it may interfere with the release and/or degradation of von Willebrand factor multimers.…”
Section: Discussionmentioning
confidence: 99%
“…The disease occurs more frequently in younger women. In 10-31% of cases it is associated with pregnancy [3,4] and is characterized by intraluminal platelet aggregation in the microcirculation causing vascular occlusion, arrest of blood flow, hypoxia, and tissue damage [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Few cases of TTP (10%) occur during the first trimester [1,2], the majority occurring at the time of delivery or during post-partum period [4,6]. Until the effectiveness of plasma infusion and plasma exchange was recognized, TTP was associated with a mortality rate of 95% and, in case of pregnancy-related TTP, the maternal survival was rare and the fetal mortality rate approached 80% [9].…”
mentioning
confidence: 99%
“…Plasma exchange should be continued for several days after normalization of platelets count and resolution of hemolysis is documented [3][4][5]9]. It has now been demonstrated that pregnancy does not impair the response to plasmapheresis and that plasmapheresis does not impair the outcome of pregnancy [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation